An Adaptive Stable Link Selection Algorithm for Mobile Ad Hoc Networks - Hui Zhang; Yu-ning Dong (Eighth ACIS International Conference on Software Engineering, Artificial Intelligence, Networking, and Parallel/Distributed Computing (SNPD 2007): 30 July - 01 August 2007 / Qingdao, China, 2007)
An adaptive strategy based stable link selection algorithm is proposed in this paper, in which the stable neighbor metric and local movement metric are defined. On the basis, the stability probability of each link is computed adoptively to find the most stable link or route in a route discovery. The simulation results show that our algorithm can effectively adapt to the network conditions, and outperforms the longevity factor based algorithm as well as the residual lifetime based algorithm in selecting stable links.